2017
DOI: 10.1242/jeb.146779
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate regulation in diving sea lions: the vagus nerve rules

Abstract: Recent publications have emphasized the potential generation of morbid cardiac arrhythmias secondary to autonomic conflict in diving marine mammals. Such conflict, as typified by cardiovascular responses to cold water immersion in humans, has been proposed to result from exercise-related activation of cardiac sympathetic fibers to increase heart rate, combined with depth-related changes in parasympathetic tone to decrease heart rate. After reviewing the marine mammal literature and evaluating heart rate profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 120 publications
2
29
0
1
Order By: Relevance
“…Variable heart rates can also occur if the spontaneous depolarization rates of pacemaker cells in the atria, atrio‐ventricular junction, or even the ventricles are faster than that of the sinus node (Catalano , Ponganis et al . ). Such ECG complexes (premature atrial and ventricular complexes; supraventricular, junctional and ventricular rhythms) were not seen in these records.…”
Section: Apneic Heart Rates During Trained Breath Holds Of Three Killmentioning
confidence: 97%
See 1 more Smart Citation
“…Variable heart rates can also occur if the spontaneous depolarization rates of pacemaker cells in the atria, atrio‐ventricular junction, or even the ventricles are faster than that of the sinus node (Catalano , Ponganis et al . ). Such ECG complexes (premature atrial and ventricular complexes; supraventricular, junctional and ventricular rhythms) were not seen in these records.…”
Section: Apneic Heart Rates During Trained Breath Holds Of Three Killmentioning
confidence: 97%
“…), this study suggests that benign fluctuations in heart rate are common in diving animals (Ponganis et al . ).…”
Section: Apneic Heart Rates During Trained Breath Holds Of Three Killmentioning
confidence: 97%
“…Parasympathetic stimulation results in an elevated ST segment, and it has been suggested the mechanism is through a reduction in I Ca−L during the action potential plateau ( Litovsky and Antzelevitch, 1990 ; Meregalli et al, 2005 ). Enhanced vagal tone can also lead to reduced heart rate ( Coote and White, 2015 ; Ponganis et al, 2017 ). Studies from healthy rat and rabbit myocardium indicate that a decrease in heart rate, in turn, results in a decrease in intracellular calcium amplitude, a decrease in developed force of contraction, and increased MCS ( Hiranandani et al, 2006 ; Varian and Janssen, 2007 ).…”
Section: Vagal Tone and Risk Of Arrhythmias In Brugada Syndromementioning
confidence: 99%
“…Other factors that we could not measure, such as respiration rate, likely mask a stronger relationship. The regulation of f H in sea lions during surface swimming probably reflects a typical mammalian exercise response with an increase in f H secondary to parasympathetic (vagus nerve) withdrawal at low exercise intensity, and, additionally, to sympathetic activation (cardiac accelerator fibers) at higher workloads (Michael et al, 2017;Ponganis et al, 2017). In contrast, during the surface intervals following dives reaching depths between 50 and 300 m, f H was much higher, typically 130-150 beats min −1 , even though the sea lions exhibited similar surface MSA after both shallow and deep dives.…”
Section: Discussion Dive Duration Depth and Activity Influence F Hmentioning
confidence: 99%
“…The dive response is a dynamic process, which is influenced by a variety of factors such as dive duration, depth, exercise intensity, temperature and even volition (Davis and Williams, 2012;Elmegaard et al, 2016;Kaczmarek et al, 2018;McDonald et al, 2017;McDonald and Ponganis, 2014;Noren et al, 2012;Thompson and Fedak, 1993;Williams et al, 2015). Based on recent publications that emphasized the potential role of both exercise and depth in regulation of the dive response of marine mammals (Davis and Williams, 2012;Williams et al, 2015), Ponganis et al (2017) reviewed the literature to examine how the parasympathetic and sympathetic nervous systems interact during controlled dive studies, and concluded that in laboratory-based studies (a) the parasympathetic nervous system dominated over the sympathetic nervous system in the regulation of heart rate ( f H ) during dives (Elliott et al, 2002;Jones, 1995, 1996), (b) changes and fluctuations in f H were primarily due to changes in parasympathetic activity (Blix and Folkow, 1983;Butler and Jones, 1997), and (c) exercise, changes in lung volume and volitional control were three primary factors that likely influence the parasympathetic response during a dive (Angell-James et al, 1981;Elmegaard et al, 2016;Ridgway et al, 1975;Signore and Jones, 1996).…”
Section: Introductionmentioning
confidence: 99%